Interdisciplinary Perspectives on Identification in a Post-Soviet Society (Herald of Journalism, 2021)
The article is devoted to the urgent problem of national identity, within the post-Soviet information space, when the gaps in the written history of the peoples referred to in the USSR as “nomadic” like Kazakhs faced the need to reanimate the “white pages” of the distant past. In this regard, the purpose of the study: relying on interdisciplinary methods, we will turn to proto-languages and proto-migration processes in Eurasia to determine the general development of the regions and peoples inhabiting them. The originality of the study lies in the discovery of similarities in the social structures, language and culture of the ancient Turks of the Great Steppe and the Celts of Ireland. The philosophical approach made it possible to interpret the mentions of the parallels in the development of both found in earlier works by European scholars-Farabi scholars and orientalists.On the scientific and practical significance of the work, the authors made presentations at the International Scientific Seminar in March 2020. The primary results are recommended to be applied in the practice of teaching at universities for the training of social and humanitarian specialists.The main results and analysis, the conclusions of the research work can be briefly characterized as the identification of previously poorly studied social and ethnocultural phenomena from a historical and philosophical perspective.The value of the study can be described as a definite contribution of this scientific work to Turkology and philosophical understanding of universal history and mass migrations. The practical significance of the results of the work is to expand interdisciplinary projects in order to systematize these sources according to the identity of the Turkic peoples.